2015
DOI: 10.1080/10376178.2016.1157028
|View full text |Cite
|
Sign up to set email alerts
|

Living with pain in ankylosing spondylitis: a qualitative study

Abstract: Added to being asked about the quantity of pain, patients with AS should be questioned about how pain affects their lives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 51 publications
1
38
0
Order By: Relevance
“…Within the workplace, a major barrier to worker retention is discord with managers and colleagues [109,110]. Research suggests that people working with MSK conditions perceive their colleagues to view them as a liability in the workplace, and believe that their 'healthy' colleagues prefer for 'sick' employees to experience high absenteeism rates, rather than presenting to work [93].…”
Section: The Organisationmentioning
confidence: 99%
“…Within the workplace, a major barrier to worker retention is discord with managers and colleagues [109,110]. Research suggests that people working with MSK conditions perceive their colleagues to view them as a liability in the workplace, and believe that their 'healthy' colleagues prefer for 'sick' employees to experience high absenteeism rates, rather than presenting to work [93].…”
Section: The Organisationmentioning
confidence: 99%
“…AS is also a young-onset disease, with initial symptoms occuring before the age of 40 in about 90% of patients [7]. Along with its physical impacts on patients' pain and disability [8][9][10], studies have also shown the association of AS with physical complications including various cardiovascular diseases [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…46 While we found that work colleagues were a source of considerable support in enabling task flexibility, other studies have reported that unsatisfactory or slow work was a source of potential conflict with colleagues and employers. 49 The differing ways in which people now participate with work also raise questions about how we define presenteeism, sick absence and fitness for work.…”
Section: Discussionmentioning
confidence: 99%